Can vaccines for contagious agalactia reduce disease progression in infected animals: a preliminary study?. Issue 4 (18th October 2018) - Loria, Guido Ruggero; Puleio, Roberto; Agnello, Stefano; Marogna, Gavino; Nicholas, Robin A J
Abstract : A flock of sheep in Central Sicily was affected by a severe outbreak of contagious agalactia (CA) caused by Mycoplasma agalactiae, affecting nearly 30% resulting in a large drop in milk production. Many ewes had warm and swollen udders that often became sclerotic and was accompanied by keratoconjunctivitis and arthritis in both adults and young. As antibiotic treatment appeared ineffective, the whole flock was given two doses of an inactivated vaccine against M agalactiae two weeks apart. A small group was selected for close examination and additional tests. A fortnight after the last vaccination mycoplasma excretion fell in all but one of the selected ewes and was undetectable in all but two animals two weeks after that. In nearly all the selected ewes, there was an improvement in milk quality and udder condition. This work provided preliminary evidence for the continued use of CA vaccines to slow or prevent disease progression.